A Psyllid, Boreioglycaspis melaleucae Moore (Insecta: Hemiptera: Psyllidae) - Susan A. Wineriter; Susan E. Halbert; James P. Cuda (EDIS)
The introduced tree Melaleuca quinquenervia (Cav.) S.T. Blake (Myrtaceae), known as paperbark, punktree or melaleuca, is an aggressive invader of many South Florida ecosystems, including the Everglades. Melaleuca is considered a pest because it displaces native vegetation and degrades wildlife habitat; it also creates fire hazards and can cause human health problems (Rayamajhi et al. 2002). The USDA/ARS, with federal and state permission, introduced the psyllid Boreioglycaspis melaleucae into Broward County, Florida, in February 2002 as a potential biocontrol agent of melaleuca. This document is EENY-300 (originally published as DPI Entomology Circular 410- updated for this publication), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2003.